Straight A's : Asian American College Students in Their Own Words - Akatsuka, Neal K. Adolph, 1987-; Yano, Christine Reiko (Book collections on Project MUSE., 2018)
The American Dream of success for many Asian Americans includes the highest levels of education. But what does it mean to live that success? In Straight A's Asian American students at Harvard reflect on their common experiences with discrimination, immigrant communities, their relationships to their Asian heritage, and their place in the university. They also explore the difficulties of living up to family expectations and the real-world effects of the "model minority" stereotype. While many of the issues they face are familiar to a wide swath of college students, their examinations of race, ethnicity, gender and sexuality, and culture directly speak to the Asian American experience in U.S. higher education. Unique and revealing, intimate and unreserved, Straight A's furthers the conversation about immigrant histories, racial and ethnic stereotypes, and multiculturalism in contemporary American society